Characterization of Hepatocellular Carcinoma Cell Lines Using a Fractionation-Then-Sequencing Approach Reveals Nuclear-Enriched HCC-Associated lncRNAs - Chow, Eugene Yui-Ching; Zhang, Jizhou; Qin, Hao; Chan, Ting-Fung (Frontiers in Genetics, 2019)
1.1 Background Advances in sequencing technologies have greatly improved our understanding of long non-coding RNA (lncRNA). These transcripts with lengths of >200 nucleotides may play significant regulatory roles in various biological processes. Importantly, the dysregulation of better characterized lncRNAs has been associated with multiple types of cancers, including hepatocellular carcinoma (HCC). There are many studies on altered lncRNA expression levels, very few, however, have focused on their subcellular localizations, from which accumulating evidences have indicated their close relationships to lncRNA functions. A transcriptome-wide investigation of the subcellular distributions of lncRNAs might thus provide new insights into their roles and functions in cancers. 1.2 Results In this study, we subjected 8 patient-derived HCC cell lines to subcellular fractionation and independently sequenced RNAs from the nuclear and cytoplasmic compartments. With the integration of tumor and tumor-adjacent RNA-seq dataset of liver hepatocellular carcinoma (LIHC) from The Cancer Genome Atlas (TCGA), de novo transcriptome assembly and differential expression analysis were conducted successively and identified 26 nuclear-enriched HCC-associated lncRNAs shared between the HCC samples and the TCGA dataset, including the reported cancer driver PXN-AS1. The majority of nuclear-enriched HCC-associated lncRNA are associated with the survival outcomes of HCC patients, exhibited characteristics similar to those of many experimentally supported HCC prognostic lncRNAs, and were co-expressed with protein-coding genes that have been linked to disease progression in various cancer types. 1.3 Conclusion We adopted a fractionation-then-sequencing approach on multiple patient-derived HCC samples and identified nuclear-enriched, HCC-associated lncRNAs that could serve as important targets for HCC diagnosis and therapeutic development. This approach could be widely applicable to other studies into the disease etiologies of lncRNA.